A Document Concerning Tre Waqf of Grazi Husref-Bey in Sarajevo From 1252/1836 - Çetin, Atilla (Prilozi za orijentalnu filologiju, 2017)
This brief paper comprises the transcription of two documents concerning the waqf of Ghazi Husref-bey, kept at the library of the Istanbul newspaper „Tercüman“, in its collection of Ottoman documents. The first document deals with the income and expenditures of the waqfin the years before and after the fire of 1247/1831, in which the waqfreal-estate was destroyed. The waqf recovered quickly after this disaster, its buildings were repaired, so that in 1251/1835-6 the waqfmade a profit in the managing of its affairs. The document emphasises that the instructions of the testator should be strictly followed, and the person in charge as requested to act in the best interests of the waqf. At that time kaymekam, „one of the most prominent men of the said town (Sarajevo)“ was in charge, since the muteveli (member of the famjly hereditary entrusted with the guardianship of the waqf) was under age. Another document is connected with the above: a survey of income and expenditures of the waqfin the period between 1. muharram 1248/May 31, 1832 tilI the end of 1251/ April 17, 1836. At the end, the total annual income (69.368 groshen), and expenditure (35.388 groshen) are given, which shows a surplus income of 33.980 groshen.